Soluble sugar, organic acid and phenolic composition and flavor evaluation of plum fruits - Qiao Xiao; Shiyuan Ye; Hao Wang; Shanshan Xing; Wenli Zhu; Haonan Zhang; Jiawei Zhu; Changbing Pu; Dongqi Zhao; Qiong Zhou; Jin Wang; Lijin Lin; et al. (Food Chemistry: X)
Plums (Prunus salicina and Prunus domestica) are prevalent in southwestern China, and have attracted interest owing to their delectable taste and exceptional nutritional properties. Therefore, this study aimed to investigate the nutritional and flavor properties of plum to improve its nutritional utilization. Specifically, we determined the soluble sugars, organic acids, and phenolic components in 86 accessions using high-performance liquid chromatography. Notably, glucose, fructose, malic, and quinic acids were the predominant sweetness and acidity in plums, with sucrose contributing more to the sweetness of the flesh than the peel. Moreover, The peel contains 5.5 fold more phenolics than flesh, epicatechin, gallic acid, and proanthocyanidins C1 and B2 were the primary sources of astringency. Correlation and principal component analyses showed eight core factors for plum flavor rating, and a specific rating criterion was established. Conclusively, these findings provide information on the integrated flavor evaluation criteria and for enhancing optimal breeding of plums.